Neoclassical tearing mode seeding by coupling with infernal modes in low-shear tokamaks. (29th July 2016) - Kleiner, A.; Graves, J.P.; Brunetti, D.; Cooper, W.A.; Halpern, F.D.; Luciani, J.-F.; Lütjens, H.
Abstract: A numerical and an analytical study of the triggering of resistive MHD modes in tokamak plasmas with low magnetic shear core is presented. Flat q profiles give rise to fast growing pressure driven MHD modes, such as infernal modes. It has been shown that infernal modes drive fast growing islands on neighbouring rational surfaces. Numerical simulations of such instabilities in a MAST-like configuration are performed with the initial value stability code XTOR-2F in the resistive frame. The evolution of magnetic islands are computed from XTOR-2F simulations and an analytical model is developed based on Rutherford's theory in combination with a model of resistive infernal modes. The parameter Δ ′ is extended from the linear phase to the non-linear phase. Additionally, the destabilising contribution due to a helically perturbed bootstrap current is considered. Comparing the numerical XTOR-2F simulations to the model, we find that coupling has a strong destabilising effect on (neoclassical) tearing modes and is able to seed 2/1 magnetic islands in situations when the standard NTM theory predicts stability.